Fermentative losses and chemical composition of elephant grass silage added with castor bean hull - Furtado, Rafael; Carneiro, Maria Socorro; Coutinho, Danielle; Cândido, Magno; Silva, Eranildo (Revista Ciência Agronômica, 2018)
Fermentation and chemical composition of elephant grass silage was evaluated with 0, 10, 20 and 30% castor been hull based on the natural matter. The experimental design was completely randomized with five replications. Silos were weighed out during manufacture, and reweighed before and after the opening after storage for 30 days. We determined the chemical composition, specific mass and effluent and gas losses, dry matter recovery, pH and ammonia nitrogen of the silage. The specific mass, pH, dry matter content, crude protein, acid detergent fiber, total carbohydrates and cellulose increased linearly (P<0.05) with the inclusion of castor bean hull. Quadratic effect was observed for effluent and gas losses, ammonia nitrogen and non-fibrous carbohydrates with minimal point when the castor bean hull was included at 25.63; 31.19; 28.07 and 11.7%, respectively. Dry matter recovery and neutral detergent fiber adjusted to a quadratic equation with maximum point when the castor bean hull was added at 24.20 and 20.62%, respectively. The inclusion of castor bean hull in elephant grass silage reduces losses during fermentation without compromising the chemical composition when included in the ratio of up to 25%, based on the natural matter.